2018
DOI: 10.1080/21691401.2018.1527345
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumour effects of TRAIL-expressing human placental derived mesenchymal stem cells with curcumin-loaded chitosan nanoparticles in a mice model of triple negative breast cancer

Abstract: Triple-negative breast cancer (TNBC) is the most aggressive type of breast cancer with poor prognosis. Despite the emergence of new and targeted therapies for other types of breast cancer, chemotherapy, surgery and radiotherapy are the only common therapies for TNBC. Tumour necrosis factor-related apoptosis-inducing ligand (TRAIL), with selective apoptotic properties in tumour cells has been considered as a promising neoadjuvant therapy in some cancers including TNBC. The application of TRAIL in clinic has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…Hence, for improvement of the TRAIL elicited anti-tumor effects, combined use of TRAIL with various TRAIL sensitizing components (e.g., synthetic agents and natural products) has represented pronounced therapeutic outcomes. Further, the use of NPs and stem cells, in particular, human mesenchymal stem/stromal cells (MSCs), as TRAIL delivery vehicles has currently attracted rapidly evolving attention ( 30 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, for improvement of the TRAIL elicited anti-tumor effects, combined use of TRAIL with various TRAIL sensitizing components (e.g., synthetic agents and natural products) has represented pronounced therapeutic outcomes. Further, the use of NPs and stem cells, in particular, human mesenchymal stem/stromal cells (MSCs), as TRAIL delivery vehicles has currently attracted rapidly evolving attention ( 30 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…29,30 The PDMSCs have a spindle-shaped morphology with multiple mesodermal differentiation. 20 We designed to explore whether MSCs isolated from human placental tissue can differentiate into neural cells using induction medium including RA, cAMP, and forskolin supplementation as a neural induction factor, in one step of induction protocol. The PDMSCs have shown their capability in differentiating into neural-like cells, with this characteristic being identified through morphology, q-PCR, and Immunostaining.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Flow cytometry result indicated that the cells are positive for CD44, CD73, CD105, and CD90, and negative for CD45 and CD34. 20 The FTIR results showed the presence of both polymers PLLA and PCL in the hybrid nanofibrous scaffold. The peaks at 2948 and 2868 cm -1 are due to the C-H stretching, at 1758 and 1735cm-1 match up to the C=O bonding, and at 1183 cm -1 is due to the C-O bending (Fig.…”
Section: Isolation and Characterization Of Cells From The Placental Tmentioning
confidence: 95%
See 1 more Smart Citation
“…Several reports showed the capacity of engineered MSCs expressing TRAIL (MSC-TRAIL) homing to the tumor microenvironment and inducing significant tumor regression [39,40,41]. The effect of MSC-TRAIL destroying tumors was well described in pre-clinical models of glioblastoma [42], pancreatic tumor [43,44], breast cancer [45,46,47,48], and prostate cancer [49]. However, very few studies reported the anti-tumor efficacy of MSC-TRAIL in lung cancer, and its ability to inhibit cancer stem cells (CSCs) derived from NSCLC.…”
Section: Introductionmentioning
confidence: 99%